Quantification of wet Age Related Macular Degeneration in Optical Coherence Tomography Angiography images - Shingavi, Monika (INFOCOMP Journal of Computer Science, 2020)
Age-related Macular Degeneration (AMD) is a common eye condition that leads to about 8% of all blindness worldwide. It is leading cause of vision loss among people age 50 and older. Late stage AMD is divided into dry AMD and wet AMD. Drusen and Choroidal Neovascularization(CNV) are the major causes of dry and wet AMD. OCTA is recent noninvasive and safer technique that provide detailed internal and external structural information of CNVs. Detecting and analysing CNV is very effective for proper treatment and assessment of wet AMD. The proposed work aim to provide automated method and application to detect and analyse CNV region in OCTA images. Proposed methodology is divided into two modules which include CNV segmentation step based on connected component labelling algorithm and other one is CNV quantification step based on Otsu thresholding. This provides two important quantification measures namely CNV area and CNV vessel density. Performance of proposed system was measured using various parameters and was found better when compared with state of art methods. The jaccard similarity score was 0.9379 ± 0.023 and false negative rate was 0.0026 ± 0.003.